GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

GFF Civil Society Engagement Strategy Addendum - Adolescent and Youth (AY) - Global Financing Facility (Global Financing Facility, 2018)
The Global Strategy for Women’s, Children’s and Adolescents’ Health 2016-30 highlights the importance of adolescent health and well-being as being essential to achieving the Sustainable Development Goals (SDG) by 2030. For adolescents to survive, thrive and transform their societies, the global community needs to invest in their health and well-being. Today’s adolescents are well-positioned to mobilize their peers, advocate for increased resources for sexual and reproductive health and rights, influence their governments to invest in addressing their needs, and demand accountability for commitments related to their health and development. The Global Financing Facility (GFF) Civil Society Engagement Strategy (CSES) and related implementation plan provide a clear framework for civil society organizations’ (CSOs) contribution to the improvement of health outcomes through coalition strengthening, meaningful participation in multi-stakeholder country platforms responsible for coordinating health plans and their implementation,1 and coordinated action in support of the achievement of national sexual, reproductive, maternal, newborn, child and adolescent health (SRMNCAH) goals. Youth and adolescent led organizations should use the CSES as the basis for their engagement in the GFF processes both at the global and national levels. This Adolescent and Youth (AY) addendum to the CSES outlines a deliberate approach to ensuring youth representation in the processes led by the GFF Civil Society Coordinating Group2 (CSCG) to ensure their meaningful and active participation in the design, implementation, monitoring and evaluation of their country investment case.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; development partners / parceiros de cooperação; health / saúde; youth / juventude

GFF Implementation Plan for the Gff Civil Society Engagment Strategy - Global Financing Facility (Global Financing Facility, 2017)
The implementation plan for the civil society engagement strategy (CSES) is developed to provide civil society organizations in countries (CSOs) with an operational framework to strengthen their engagement in the GFF process with a view to supporting the achievement of the objectives of the GFF and national investment cases. The plan reflects and builds on, and should be read in conjunction with the CSES. It is shaped and informed by GFF country implementation experiences to date, 12345 as well as the results of a targeted 2017 survey sent to CSOs working in GFF countries. The survey was geared towards understanding: 1) the civil society landscape in countries; 2) the level of knowledge of the GFF processes by CS; 3) priority actions CS can take to strengthen their engagement in the GFF processes and to support the achievement of the RMNCAH investment cases; and 4) what resources CS might need to better engage with national platforms and planning processes and to implement the identified supportive actions. The survey was sent to 18 organizations in 12 GFF countries and had a 61% response rate.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; health / saúde